2010
DOI: 10.1590/s0100-736x2010001000013
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol influence on testicular testosterone secretion in domestic cat: An in vitro study

Abstract: Pesq. Vet. Bras. 30(10):887-890, outubro 2010 RESUMO.-[Ação do cortisol sobre a secreção de testosterona em testículos de gato doméstico: um estudo in vitro.] O objetivo deste trabalho foi investigar o efeito da hidrocortisona sobre a secreção de testosterona após cultivo in vitro dos testículos, em distintas situações de estresse (transporte) de gatos domésticos (Felis silvestris catus). Testículos foram incubados nos seguintes meios de cultura: TCM 199; TCM 199 + hCG 10 -7 M; TCM 199 + hydrocortisona 10 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The signaling pathways mediating these effects are thought to involve the peptide substance P acting on neurokinin 1 receptors, nerve growth factor, and possibly glucocorticoids, due to activation of the hypothalamic‐pituitary‐adrenocortical axis 10 . The testicular enlargement seen in the male marmoset can also be explained by a condition of stress, once a study on domestic cats revealed that acute stress increases testicular testosterone secretion 23 …”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways mediating these effects are thought to involve the peptide substance P acting on neurokinin 1 receptors, nerve growth factor, and possibly glucocorticoids, due to activation of the hypothalamic‐pituitary‐adrenocortical axis 10 . The testicular enlargement seen in the male marmoset can also be explained by a condition of stress, once a study on domestic cats revealed that acute stress increases testicular testosterone secretion 23 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a direct association has been established between cortisol and aggression in feral female cats [ 30 ]. A previous study has also shown that cortisol can increase testosterone secretion in vitro [ 31 ]. However, to date, no survey has explored the components of social behavior that may be related to GC concentrations in group-living cats.…”
Section: Introductionmentioning
confidence: 99%
“…), sejam elas comportamentais ou não. É importante ressaltar o quanto os gatos ainda são utilizados como modelos experimentais em inúmeros estudos científicos extremamente recentes, abordando assuntos como cardiomiopatias(VAN ESSEN et al, 2012) e envolvidos nas áreas de neuroanatomia(QUOC et al, 2012), psicologia (KONERDING et al, 2012 WELLS; MILLSOPP, 2012) , ecologia molecular(DEVILLARD et al, 2011), microbiologia(GERRIKAGOITIA et al, 2012) e fisiologia(GENARO;FRANCI, 2010;HOENIG et al, 2011). Assim, é um tanto surpreendente que relativa pouca atenção tenha sido voltada para o bem-estar desses animais, quando comparamos com a quantidade de material publicado para outros animais de criação(BRADSHAW; CASEY, 2005).…”
unclassified